Teenagers Perception Of Committed Relationship On Their Parents Infidelity In North Sumatra - Sauli Safitri; Lucy Pujasari Supratman (Syntax Corporation, 2023)
The purpose of this study was to describe the committed relationship on teenagers whose parents experienced an infidelity to divorced. This study uses a qualitative method with a phenomenological approach. Qualitative is one of the methods used in research that focuses on understanding the meaning of individuals or group originating from a problem in social life (Creswell, 2016). The data collection technique used in this study was to conduct interviews and observations with five informants aged 17 to 21 who live in North Sumatra. Then the data that has been collected will be analyzed by researcher to be more structed. The result of this study is a description of how parental infidelity bring an impact to the teenager’s perception in seeing a committed relationship. Divorce parents brings positive and negative impacts on teenagers. moreover, there are some things that are quite different between participants were them who has a low level of communication with their cheating parents tend to have high trust issues problems.